Monoamine Reuptake Inhibitors in Parkinson’s Disease - Philippe Huot; Susan H. Fox; Jonathan M. Brotchie (Parkinson's Disease)
The motor manifestations of Parkinson’s disease (PD) are secondary to a dopamine deficiency in the striatum. However, the degenerative process in PD is not limited to the dopaminergic system and also affects serotonergic and noradrenergic neurons. Because they can increase monoamine levels throughout the brain, monoamine reuptake inhibitors (MAUIs) represent potential therapeutic agents in PD. However, they are seldom used in clinical practice other than as antidepressants and wake-promoting agents. This review article summarises all of the available literature on use of 50 MAUIs in PD. The compounds are divided according to their relative potency for each of the monoamine transporters. Despite wide discrepancy in the methodology of the studies reviewed, the following conclusions can be drawn: (1) selective serotonin transporter (SERT), selective noradrenaline transporter (NET), and dual SERT/NET inhibitors are effective against PD depression; (2) selective dopamine transporter (DAT) and dual DAT/NET inhibitors exert an anti-Parkinsonian effect when administered as monotherapy but do not enhance the anti-Parkinsonian actions of L-3,4-dihydroxyphenylalanine (L-DOPA); (3) dual DAT/SERT inhibitors might enhance the anti-Parkinsonian actions of L-DOPA without worsening dyskinesia; (4) triple DAT/NET/SERT inhibitors might exert an anti-Parkinsonian action as monotherapy and might enhance the anti-Parkinsonian effects of L-DOPA, though at the expense of worsening dyskinesia.